Penguatan Demokrasi Lokal Melalui Penghapusan Jabatan Wakil Kepala Daerah - Suhariza, Suhariza (Mahkamah Konstitusi Republik Indonesia, 2010)
Democracy at the local level becoming a necessity for achieving the goals of regional autonomy. Furthermore, the strengthening of democracy at the local level being the significant pillar in strengthening democracy at the national level. The strategic step to consolidate democracy at the local level particulary in terms of the regional head elections is by elimination the position of deputy regional head . This paper is describes the problems about the circumtances after head local election specially the relationship between Regional Head and Deputy Regional Head along with the idea about the eliminationof the position of Deputy Regional Head.